1999
DOI: 10.1017/s0885715600010277
|View full text |Cite
|
Sign up to set email alerts
|

Barium hollandite-type compounds BaxFe2xTi8−2xO16 with x=1.143 and 1.333

Abstract: Experimental X-ray powder diffraction patterns and refined unit cell parameters for two barium hollandite-type compounds, BaxFe2xTi8−2xO16, with x=1.143 and 1.333, are reported here. Compared to the tetragonal parent structure, both compounds exhibit monoclinic distortions that increase with Ba content [Ba1.333Fe2.666Ti5.334O16: a=10.2328(8), b=2.9777(4), c=9.899(1) Å, β=91.04(1)°, V=301.58(5) Å3, Z=1, ρcalc=4.64 g/cc; Ba1.143Fe2.286Ti5.714O16: a=10.1066(6), b=2.9690(3), c=10.064(2) Å, β=90.077(6)°, V=301.98(4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…It is interesting to notice that literature indicated that the iron (Ba,Fe)-hollandite Ba 1.14 (Fe 2.28 Ti 5.71 )O 16 , i.e. a composition very close to the one studied in the present work, was monoclinic (a = 10.107 Å , b = 2.969 Å , c = 10.064 Å , b = 90.077°) [33]. However, in our case, the lines of the XRD pattern of Ba 1.16 Fe 2.32 Ti 5.68 O 16 sample (Fig.…”
Section: Characterization Methodssupporting
confidence: 76%
“…It is interesting to notice that literature indicated that the iron (Ba,Fe)-hollandite Ba 1.14 (Fe 2.28 Ti 5.71 )O 16 , i.e. a composition very close to the one studied in the present work, was monoclinic (a = 10.107 Å , b = 2.969 Å , c = 10.064 Å , b = 90.077°) [33]. However, in our case, the lines of the XRD pattern of Ba 1.16 Fe 2.32 Ti 5.68 O 16 sample (Fig.…”
Section: Characterization Methodssupporting
confidence: 76%
“…But, if the structure is monoclinic (I2/m space [8] hollandites which reported also one quadrupolar doublet at 300 K whose parameters were close to the ones of site 2. Moreover, few studies have reported a monoclinic structure for a close hollandite composition Ba 1.14 Fe 2.28 Ti 5.72 O 16 [9]. Therefore, we can wonder if our material does not display a slight monoclinic distortion not clearly detected by XRD and thus these two doublets (Figure 2a) would be related to the two different crystallographic sites.…”
Section: Resultsmentioning
confidence: 87%
“…Hollandites have the formula A x B 8 O 16 and are typically tetragonal in symmetry [8]. Structurally, they consist of double chains of edgeshared transition metal BO 6 octahedra sharing corners to form large, four-sided tunnels along the c-axis in which alkali or alkaline earth cations reside.…”
Section: Introductionmentioning
confidence: 99%